بين مفهومي الجهاد والإرهاب: دراسة في المفهوم والأهداف لحركة القاعدة وتنظيم داعش أنموذجا: Between Jihād and Terrorism: An Introspection on Its Concepts and Purposes with Reference to the al-Qaeda and ISIS Movements - Mansor, Muhamad Sayuti; Mohamad Azwan Kamarudin (Jurnal Fiqh, 2021)
In the aftermath of the September 11 attacks, Islam has fell victim to the allegation that relates it to terrorism. This is due to the rise of terrorist movements such as al-Qaeda and ISIS that claim to be representing Islam and pursuing the holy war (jihād) to establish an Islamic caliphate (al-khilāfah al-Islāmiyyah). These terrorist movements also used the same terms and concepts that can be found in the traditional Muslim scholarship, such as the abode of Islam and the abode of war (dār al-Islām wa dār alḥarb), loyalty and disavowal (al-walā’ wa al-barā’), and excommunicating Muslims (takfīr). Thus, this study seeks to analyse these two concepts of jihād and terrorism (irhāb) to locate both their similarities and differences. Comparison is made from several aspects such as etymology and history and lastly its application in our contemporary reality in relation to other relevant terms and concepts as mentioned above. This study finds that there are substantial differences between jihād and irhāb, and it is the failure to grasp the ever evolving and developing nature of Islamic law (fiqh) and the contemporary reality that led to this confusion.